Composite outcome of oral azvudine vs. nirmatrelvir-ritonavir in COVID-19 patients: a retrospective cohort study - Chen, Jingxia; Liu, Zhengyue; Liu, Ruolin; Su, Chengxin; Yang, Yunyun; Wang, Zhuo (Frontiers in Pharmacology, 2025)
ObjectiveTo explore the effectiveness and safety of azvudine and nirmatrelvir-ritonavir in a real-world setting.MethodsThis retrospective cohort study included adult patients with confirmed COVID-19 who received azvudine or nirmatrelvir-ritonavir treatment at Shanghai Changhai Hospital between 1 November 2022, and 30 March 2023. Data were collected from the hospital’s electronic medical record system using a standardized data extraction form. Propensity score matching (PSM) was used to control for potential confounding factors. The primary outcome was the incidence of composite disease progression, defined as the occurrence of death, ICU admission, invasive respiratory support, or high-flow oxygen therapy. Multivariable Cox regression analysis was performed to identify the factors independently associated with the composite progression outcomes.ResultsThis study included 476 patients: 296 treated with azvudine and 180 treated with nirmatrelvir-ritonavir. After PSM, 139 patients were included in each group. There were no statistically significant differences between the two groups regarding the composite outcome (log-rank: P = 0.475; HR: 0.82, 95%CI: 0.46–1.43, P = 0.478), death (log-rank: P = 0.526; HR: 0.82, 95%CI: 0.44–1.52, P = 0.528), ICU admission (log-rank: P = 0.525; HR: 0.69, 95%CI: 0.22–2.18, P = 0.526), invasive ventilation (log-rank: P = 0.814; HR: 1.20, 95%CI: 0.27–5.39, P = 0.814), or oxygen use (log-rank: P = 0.370; HR: 1.44, 95%CI: 0.65–3.18, P = 0.372). The multivariable analysis showed that the antiviral drug (HR = 0.861, 95%CI: 0.486–1.524, P = 0.607) was not independently associated with the composite outcome. Only severe COVID-19 was independently associated with the composite outcome (HR = 3.322, 95%CI: 1.569–7.031, P = 0.002). The safety outcomes were similar between the two groups.ConclusionThis real-world study demonstrates comparable efficacy and safety profiles between azvudine and nirmatrelvir-ritonavir in treating COVID-19 patients, regardless of disease severity or baseline characteristics. The findings support azvudine as a practical alternative for treatment selection, particularly in resource-constrained settings or for patients with contraindications to specific therapies. Clinical decisions should prioritize patient-specific needs, accessibility, and cost-effectiveness. Further large-scale prospective studies are needed to validate these observations and refine subgroup-specific treatment strategies.